2021
DOI: 10.3389/feart.2021.686272
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Performance of Regional Earthquake Early Warning Algorithms in Europe

Abstract: Several earthquake early warning (EEW) algorithms have been developed worldwide for rapidly estimating real-time information (i.e., location, magnitude, ground shaking, and/or potential consequences) about ongoing seismic events. This study quantitatively compares the operational performance of two popular regional EEW algorithms for European conditions of seismicity and network configurations. We specifically test PRobabilistic and Evolutionary early warning SysTem (PRESTo) and the implementation of the Virtu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Studies have shown that implementing a PRESTo in Italy could theoretically deliver alert messages within approximately 5 to 10 s, with maximum lead times for implementing security measures at a distant target of about 25 s [16]. This system, therefore, represents the current state-of-the-art in regional EEW technology in the country and is one of the most used software solutions for EEW in Europe [18]. Besides PRESTo, the other most widely used regional EEW software in Europe is VS(SC) (Virtual Seismologist in SeisComP) [21].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that implementing a PRESTo in Italy could theoretically deliver alert messages within approximately 5 to 10 s, with maximum lead times for implementing security measures at a distant target of about 25 s [16]. This system, therefore, represents the current state-of-the-art in regional EEW technology in the country and is one of the most used software solutions for EEW in Europe [18]. Besides PRESTo, the other most widely used regional EEW software in Europe is VS(SC) (Virtual Seismologist in SeisComP) [21].…”
Section: Related Workmentioning
confidence: 99%
“…VS(SC) incorporates phase picking using the Short-Time Average over Long-Time Average (STA/LTA) algorithm [22], and location and magnitude estimation algorithms integrated in the Seiscomp software module [23]. It has been shown that PRESTo is ultimately the best choice for regional EEW compared to the VS(SC) module [18], as it provides better short-term predictions, a key requirement for EEW. Furthermore, PRESTo has undergone extensive implementation and testing in multiple regions and scenarios, including Southern Italy, Turkey, Romania, Southern Iberia, Austria, and Slovenia [18].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Point source assessments verify EEW algorithms for magnitude and hypocenter accuracy (e.g., Cua et al, 2009;Chen et al, 2015;Massin et al, 2021). Alert assessments are performed to prevent errors during operations or simulations (e.g., Chen et al, 2019;Chung et al, 2019;Zuccolo et al, 2021). However, management aspects require a comprehensive review of the overall EEW.…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing the time difference between primary and secondary seismic waves, they send warnings once an earthquake is detected. This allows immediate actions like unlocking building exits, managing power grids, and adjusting operations in critical facilities like hospitals and nuclear power plants [2].…”
Section: Introductionmentioning
confidence: 99%